2006
DOI: 10.1590/s0101-31222006000300018
|View full text |Cite
|
Sign up to set email alerts
|

Seed anatomy and germination of Phoenix roebelenii O'Brien (Arecaceae)

Abstract: -The objective of this study was to investigate the morphology, anatomy and germination behaviour of Phoenix roebelenii seeds. Biometric data were obtained by measuring 100 seeds extracted from recently harvested fruits and air-dried for one day. Four replications of 50 seeds each were previously treated with Vitavax-Thiran and then put to germinate in Sphagnum sp. in plastic trays at room temperature. Morphological details of the seeds were documented with the help of a scanning electronic microscope and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
0
14
0
3
Order By: Relevance
“…Asif et al, (2001) concluíram que a luz não afetou a germinação de embriões de Musa acuminata, porém, o cultivo no escuro atrasou a emissão da parte aérea e favoreceu o enraizamento. A emissão de raízes deve ser considerada como variável chave para a avaliação da cultura de embriões de palmeiras (Melo, 2000), uma vez que, em várias espécies, ocorre a imaturidade do embrião, relacionada com a indiferenciação da radícula, como em Washingtonia filifera (Demason, 1988), Euterpe precatoria (Aguiar & Mendonça, 2002) e Phoenix roebelenii (Iossi et al, 2006). Melo et al (2001) não obtiveram enraizamento em plântulas de guarirobeira até os 110 dias de cultivo.…”
Section: Resultsunclassified
“…Asif et al, (2001) concluíram que a luz não afetou a germinação de embriões de Musa acuminata, porém, o cultivo no escuro atrasou a emissão da parte aérea e favoreceu o enraizamento. A emissão de raízes deve ser considerada como variável chave para a avaliação da cultura de embriões de palmeiras (Melo, 2000), uma vez que, em várias espécies, ocorre a imaturidade do embrião, relacionada com a indiferenciação da radícula, como em Washingtonia filifera (Demason, 1988), Euterpe precatoria (Aguiar & Mendonça, 2002) e Phoenix roebelenii (Iossi et al, 2006). Melo et al (2001) não obtiveram enraizamento em plântulas de guarirobeira até os 110 dias de cultivo.…”
Section: Resultsunclassified
“…Date fruits are ellipsoidal to ovoid or almost cylindrical. Dimensions of dates are variable, ranging from 10 × 5 mm in P. roebelenii O'Brien (Iossi, Vitti & Rubens, ), to 75 × 35 mm in P. dactylifera ‘Medjool’.…”
Section: Introductionmentioning
confidence: 99%
“…The germination in many species is dependent on seed treatments that promote post-abscission embryonic development (Baskin and Baskin 1998;Hartmann et al 2002). Demason (1988a) observed that the root pole of the embryo of W. filifera was less developed that it was not possible to determine the inclination of the embryo axis; similar situations were reported for Euterpe precatoria (Aguiar and Mendonça 2003) and Phoenix roebelenii (Iossi et al 2006). Additionally, root system development in species such as C. nucifera (Lédo et al 2007) and S. oleracea (Melo et al 2001) is difficult even when the embryos are cultivated in vitro, and requires hormonal stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…Henderson (2006) pointed out that there are many morphological patterns in palm embryos and seedlings, and that germination processes could only be accurately described through a detailed association of morphological and anatomical characteristics. In spite of the fact that there has been a certain amount of published research focusing on the structure and histochemistry of palm embryos (Demason and Thomson 1981;Demason 1988a;Panza et al 2004;Moura et al 2010), morphological characterization of the seedlings (Gentil and Ferreira 2005;Charlo et al 2006), and morphological and anatomical evaluations of the embryos and seedlings (Demason 1984(Demason , 1985Aguiar and Mendonça 2002;Henderson 2006;Iossi et al 2006) are still far from being complete (see Panza et al 2004).…”
Section: Introductionmentioning
confidence: 99%